CHALLENGES AND STRATEGIES IN IMPLEMENTING THE INDEPENDENT CURRICULUM: A CASE STUDY OF MTS INSAN MADANI, SITUBONDO - Hoirotun, Hoirotun; Permatasari, Intan; Gufron, Ali; Riskiyatin, Riskiyatin; Surur, Miftahus (Journal on Research and Review of Educational Innovation, 2024)
This study examines the implementation of the independent curriculum in the context of educational units in rural areas, specifically at MTs Insan Madani in Situbondo Regency. Employing a qualitative research approach and the Systematic Literature Review (SLR) method, this research synthesizes data collected through documents, images, and audiovisual materials. The findings highlight that while the independent curriculum aims to provide a practical and communicable learning experience, its implementation faces challenges. Key issues include a lack of understanding among teachers and the need for adaptation to available resources and curriculum changes. The study concludes that empowering teachers through targeted strategies and continuous training is critical to achieving the curriculum's goals.